Gender, social capital and information exchange in rural Uganda - Katungi, Enid; Edmeades, Svetlana; Smale, Melinda (Wiley, 2008)
Changing agricultural research and extension systems mean that informal mechanisms of information diffusion are often the primary source of information about improved seed and practices for farmers in sub‐Saharan Africa. This paper investigates the interactions between gender, social capital and information exchange in rural Uganda. Within the framework of farmer‐to‐farmer models, we conceptualise the informal information diffusion process to comprise social capital accumulation and information exchange. We assume that each agent participates in information exchange with a fixed (predetermined) level of social capital and examine how endowments of social capital influence information exchange, paying close attention to gender differences. A multinomial logit model is used to analyse multiple participation choices of information exchange facing the farmer. Findings demonstrate that social capital is an important factor in information exchange, with men generally having better access to social capital than women. We also find strong evidence in support of group‐based technology dissemination systems.